2012
DOI: 10.7577/nbf.479
|View full text |Cite
|
Sign up to set email alerts
|

Different forms of assessment and documentation in Swedish preschools

Abstract: The aim is to describe and discuss documentation and assessment practices in Swedish preschools from a didaktik perspective. What different forms of documentation and assessment are found in the preschools? Preschools in both urban and rural municipalities are included in the selection. Document and textual analysis are used. A varied multi-documentation emerge. The multi-documentation at each preschool expose that preschool teachers seem to switch between different forms of documentation and assessment, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 21 publications
0
18
0
13
Order By: Relevance
“…With the use of one local template for systematic quality development work, certain aspects of preschool quality were brought forward. While previous research has shown that documentation focuses on individual children when using individual development plans, portfolios, and sometimes pedagogical documentation (Vallberg Roth, 2012), in this study a different model produced other aspects of quality that did not focus on individual children but instead on teachers' work and children's interests or in(tra)ests. With this article I argue that it is important for anyone working with systematic quality development documentation in preschool to consider what quality can become, and how local templates, curriculum, photos, national guidelines, research, and doubtless other things as well play an active part in constructing preschool quality.…”
Section: Concluding Thoughtsmentioning
confidence: 80%
“…With the use of one local template for systematic quality development work, certain aspects of preschool quality were brought forward. While previous research has shown that documentation focuses on individual children when using individual development plans, portfolios, and sometimes pedagogical documentation (Vallberg Roth, 2012), in this study a different model produced other aspects of quality that did not focus on individual children but instead on teachers' work and children's interests or in(tra)ests. With this article I argue that it is important for anyone working with systematic quality development documentation in preschool to consider what quality can become, and how local templates, curriculum, photos, national guidelines, research, and doubtless other things as well play an active part in constructing preschool quality.…”
Section: Concluding Thoughtsmentioning
confidence: 80%
“…Buldu (2010) and Bjervås (2011) have found pedagogical documentation to be a possible way to do formative assessment, which looks forward and supports further learning, in contrast to summative assessment, which looks back at what has been achieved (Bjervås, 2011). Summative assessment can be seen as an assessment of learning while formative assessment is an assessment for learning (Vallberg Roth, 2012). In Bjervås's (2011) study, teachers saw documentation as a way for children's voices to be heard and as a way to make children aware of their own learning and their competences, which is something completely different from testing, assessing or measuring.…”
Section: Research On (Preschool) Documentationmentioning
confidence: 99%
“…In the Swedish preschool curriculum there are no goals to achieve; instead, the curriculum contains goals to strive for (Vallberg-Roth, 2012). Vallberg Roth (2012 proposes the concept of transformative assessment, which is understood as a more flexible concept.…”
Section: Research On (Preschool) Documentationmentioning
confidence: 99%
See 2 more Smart Citations